2021
DOI: 10.1080/19490976.2020.1869503
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fructooligosaccharide metabolism and fructooligosaccharide-degrading enzymes in human commensal butyrate producers

Abstract: Butyrate produced by gut microbiota has multiple beneficial effects on host health, and oligosaccharides derived from host diets and glycans originating from host mucus are major sources of its production. A significant reduction of butyrate-producing bacteria has been reported in patients with inflammatory bowel diseases and colorectal cancers. Although gut butyrate levels are important for host health, oligosaccharide metabolic properties in butyrate producers are poorly characterized. We studied the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…GH32 enzymes in the strains were sucrose-6-phosphate hydrolase (S6PH) and genes encoding phosphotransferase systems (PTSs) were adjacent to those encoding the S6PHs. S6PH is one of the most characterized enzymes to hydrolyze sucrose and kestose with or without phosphorylation in gut microbes [ 3 ]. Alignment of amino acid sequences of the GH32 proteins revealed that one of the GH32 proteins in L. gasseri (gene ID, 397) had one amino acid substitution (N to G) in the NDPNG motif (GDPNG) ( Figure 3 ), which is one of the key regions for its hydrolase activity of GH32 [ 31 ], whereas others conserved this motif.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GH32 enzymes in the strains were sucrose-6-phosphate hydrolase (S6PH) and genes encoding phosphotransferase systems (PTSs) were adjacent to those encoding the S6PHs. S6PH is one of the most characterized enzymes to hydrolyze sucrose and kestose with or without phosphorylation in gut microbes [ 3 ]. Alignment of amino acid sequences of the GH32 proteins revealed that one of the GH32 proteins in L. gasseri (gene ID, 397) had one amino acid substitution (N to G) in the NDPNG motif (GDPNG) ( Figure 3 ), which is one of the key regions for its hydrolase activity of GH32 [ 31 ], whereas others conserved this motif.…”
Section: Resultsmentioning
confidence: 99%
“…They are usually commercialized as a mixture of degrees of polymerization (DP) of 3 and 4—i.e., 1-kestose [kestose, Fur (β2–1) Fur (β2–1α) Glc] and nystose [Fur (β2–1) Fur (β2–1) Fur (β2–1α) Glc]—respectively, with trace DP5 FOS, fructosylnystose. Among the components, kestose is a promising prebiotic for the stimulation of beneficial gut microbes, including bifidobacteria and butyrate producers [ 2 , 3 ]. Although the impact of oligosaccharides on the growth of beneficial gut microbes and probiotic strains is widely known, limited studies have addressed the impact of oligosaccharides, especially kestose, on the physiological properties of such bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant with the fall in cellulolytic bacteria concentrations, our sequencing analysis revealed a decrease in the relative abundances of several potentially fibrolytic taxa, notably Lachnospiraceae ( Lachnospiraceae ND3007 group , Lachnospiraceae NK4A136 group , Lachnospiraceae UCG-008 ) [ 37 ]. The relative abundance of several fiber degraders such as the Eubacterium ruminantium group [ 38 ], the recently defined Agathobacter [ 39 , 40 ], and Roseburia [ 41 , 42 ] also fell at D2. The relative abundances of Spirochaetes and its lower phylogenetic levels dropped too.…”
Section: Discussionmentioning
confidence: 99%
“…Although distinct in structure from Gram-negative systems, prominent Firmicutes and Actinobacteria members elaborate additional cell surface-associated systems for the utilisation of polysaccharides, which are often built around enzymes with catalytic domains, similar to those of Bacteroidetes [ 48 ]. Substrate-specific gene clusters targeting a variety of plant- and host-based glycans were identified in the genomes of Eubacterium rectale and Roseburia species as Gram-positive PUL (gpPUL) [ 54 , 68 , 69 ]. The gpPUL contain carbohydrate transport systems are mostly adenosine triphosphate (ATP)-binding cassette (ABC), major facilitator superfamily (MFS), and phosphoenolpyruvate-phosphotransferase system (PTS) transporters.…”
Section: The Gut Microbiota: An Ecosystem Designed For Carbohydrate B...mentioning
confidence: 99%